2018
DOI: 10.3389/fpsyg.2017.02312
|View full text |Cite
|
Sign up to set email alerts
|

Musical Agency during Physical Exercise Decreases Pain

Abstract: Objectives: When physical exercise is systematically coupled to music production, exercisers experience improvements in mood, reductions in perceived effort, and enhanced muscular efficiency. The physiology underlying these positive effects remains unknown. Here we approached the investigation of how such musical agency may stimulate the release of endogenous opioids indirectly with a pain threshold paradigm.Design: In a cross-over design we tested the opioid-hypothesis with an indirect measure, comparing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 57 publications
(99 reference statements)
0
22
0
2
Order By: Relevance
“…[ 10 ] However, this effect has been demonstrated only in patients who actively practice music as opposed to only listen to music. [ 11 ] In critically ill patients receiving mechanical ventilation (MV), a Cochrane metaanalysis found that music decreased anxiety, heart rate, respiratory rate, and blood pressure. [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] However, this effect has been demonstrated only in patients who actively practice music as opposed to only listen to music. [ 11 ] In critically ill patients receiving mechanical ventilation (MV), a Cochrane metaanalysis found that music decreased anxiety, heart rate, respiratory rate, and blood pressure. [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence has shown that Jymmin TM can more strongly increase mood (Fritz et al, 2013b), which probably relates to findings that, postintervention, it leads to increased pain threshold (Fritz et al, 2018) and decreased perceived exertion after physical exercise (Fritz et al, 2013a). This probably relates to endorphin release (Fritz et al, 2018). In the current experiment, we did not focus on investigating mood effects of the intervention and only assessed this using a single-item visual analog scale.…”
Section: Discussionmentioning
confidence: 93%
“…By using this method, participants are able to generate music as a by-product of exercising with traditional training machines such as a lat pull-down, stepper, ab-trainer, and other machines commonly used in weight training, as well as with gymnastics movements. Jymmin TM has previously been shown to have certain cognitive effects such as heightening mood (Fritz et al, 2013b), reducing perceived exertion (Fritz et al, 2013a), increasing the aesthetic evaluation of music (Fritz et al, 2016), increasing perception of self-efficacy (Fritz et al, 2015), and decreasing the perception of pain (Fritz et al, 2018). A physiological effect at muscle level that seems to relate to greater muscle efficiency/muscle relaxation has also been reported (Fritz et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with past work showing that music does not have a meaningful effect when anxiety and pain levels are high during pre and post-surgery contexts [ 12 , 13 , 44 ]. Recent study of Fritz et al [ 45 ] also addressed that a pain reducing effect of music agency in combination with physical exercise depended on individual pain sensitivity. Thus, when attempting to utilize music as an adjuvant method for relieving pain, individual traits and mood states should be considered.…”
Section: Discussionmentioning
confidence: 99%